2013
DOI: 10.1016/j.chemgeo.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of hydrogen and carbon dioxide at Mt Etna

Abstract: This study assessed the use of an H 2 fuel cell as an H 2 -selective sensor for volcano monitoring. The resolution, repeatability, and cross-sensitivity of the sensor were investigated and evaluated under known laboratory conditions. A tailor-made device was developed and used for continuously monitoring H 2 and CO 2 at Mt Etna throughout 2009 and 2010. The temporal variations of both parameters were strongly correlated with the evolution of the volcanic activity during the monitoring period. In particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…To do this, we correlated soil CO 2 flux time series with all recorded environmental parameters. We used daily averaged values, to remove the influence of daily cycles of pressure and temperature [ Di Martino et al , ]. We found that daily average temperature and pressure exert the largest influence on soil CO 2 flux, without time delay (Table S2), as observed in other volcanic systems [ Giammanco et al , ; Liuzzo et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we correlated soil CO 2 flux time series with all recorded environmental parameters. We used daily averaged values, to remove the influence of daily cycles of pressure and temperature [ Di Martino et al , ]. We found that daily average temperature and pressure exert the largest influence on soil CO 2 flux, without time delay (Table S2), as observed in other volcanic systems [ Giammanco et al , ; Liuzzo et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Both theoretical and experimental results were applied to study the delay between CO 2 and H 2 changes recorded at Etna volcano via the continuous monitoring of the ground gases [ Di Martino et al , ]. The data were collected at the Belvedere site (Figure c), situated in a low‐temperature fumarolic field ( T < 100°C) at the edge of the Valle del Bove on the eastern flank of the volcano.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected at the Belvedere site (Figure c), situated in a low‐temperature fumarolic field ( T < 100°C) at the edge of the Valle del Bove on the eastern flank of the volcano. At Belvedere, the period between end of July and September 2010 was characterized by anomalous values for both the volcanic gas components, and the changes in the H 2 concentration preceded the changes of the CO 2 concentration [ Di Martino et al , ]. To analyze the data on the delays associated with changes in H 2 and CO 2 , the raw time series were down‐sampled using a moving average with a 17 h window.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations